Provision of Compensation for Breach of Contract in Fixed-Term Work Agreements (PKWT), A Case Study of Marvel Studios Exhibition Indonesia - Salma Mayriska Putri; Sulastri, Sulastri (Dinasti Research, 2024)
The purpose of this study is as an analysis related to how the Fixed-Tern Work Agreement (PKWT) owned by PT Tiga Karya Makmur (PT TKM) accommodates the rights of Marvel Studios Exhibition Indonesia (MSEI) employees in accordance with applicable labor regulations. In addition, analyzing the implementation of regulations for the fulfillment of compensation for breach of contract committed by PT TKM. The research method uses a type of juridical-empirical research that combines a case approach and a statue approach. Research data was collected through interviews with resource persons / parties, namely MSEI employees. The results showed that PT TKM's PKWT has fulfilled the provisions of applicable labor regulations, including important aspects such as wages, working periods, work schedules, and the rights and obligations of the parties. However, PT TKM breached the breached the contract by failing to pay its employees' wages on time, which violated Article 18 of Government Regulation Number 36 of 2021 concerning Wages. Then, PT TKM did not implement the regulations of Article 95 paragraph (2) of the Manpower Law and Article 61 of Government Regulation No. 36/2021 concerning Wages related to the payment of fines/compensation for late payment of salaries. However, both parties have mediated which resulted in a wage payment agreement. So that PT TKM has the validity to provide compensation in accordance with the amount agreed in the agreement.